Contextualizing the Impostor “Syndrome” - Feenstra, Sanne; Begeny, Christopher T.; Ryan, Michelle K.; Rink, Floor A.; Stoker, Janka I.; Jordan, Jennifer (Frontiers in Psychology, 2020)
The impostor “syndrome” refers to the notion that some individuals feel as if they ended up in esteemed roles and positions not because of their competencies, but because of some oversight or stroke of luck. Such individuals therefore feel like frauds or “impostors”. Despite the fact that impostor feelings are often linked to marginalized groups in society, to date, research predominantly approaches this phenomenon as an issue of the individual: pointing towards individuals for the roots and solutions of the “syndrome”. Drawing from a rich body of social and organizational psychology research, in this perspectives piece, we propose a shift in how scholars conceptualize and empirically examine this phenomenon. Instead of framing the insecurities of individuals belonging to marginalized groups solely as a problem that arises within these individuals, we argue that it is critical for future research to consider the important role of the environment in eliciting their impostor feelings as well. By doing so, we can address the contextual roots of individuals’ impostor feelings, and offer more structural and effective solutions.